TRAVAUX DOMESTIQUES ET ACTIVITÉS SCOLAIRES DES ÉLÈVES FILLES EN MILIEU URBAIN : UNE ANALYSE DES EFFETS - Konan, Kra Gérard Landry (European Scientific Journal, ESJ, 2015)
If the implication of the girls in the domestic activities merges with the traditional systems of initiation to the life and work, force is to note that this one sometimes enters competing with the school at the point to affect the school output of the girls. The present study was undertaken in three districts of Yopougon (Millionaire, Sicogi and Yaoséhi). It’s based on a dual quantitative and qualitative approach and is proposed to analyze the effects of domestic activities on the school Output of female students. The results indicate that when the house works are badly organized and planned in the household, that reduces the rest period of the pupils girls and prevented from having sufficient time to devote to their studies (learning, exercise of house…). They arrive then tired classifies some and do not manage any more to follow the courses correctly. What impacts negatively on their assiduity and their performance in class.